Analisis Tawasul dan Kebutuhan Manusia Terhadap Ritual Keagamaan - Al Haq, Mursyid (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
A ritual is said to be spiritually laden because of the influence it has on its practitioners. Tawasul in some Muslim circles is an important part of a prayer in supplication and munajat that is hummed to Allah. Become a connecting bridge for the fulfillment of desires. Tawasul is more accurately assessed as a gift for humans to walk towards the presence of their Lord. The controversy that later emerged from the tawasul issue was not substantial. The appearance of a ritual should not cause disputes. Monotheism that is straight and in line with religious guidance is important to pay attention to. Whether a person is polytheistic or not lies in his belief in the ware who mediates between him and Allah. Preserving religious rituals is also preserving the meaning of a series of worship without spirituality.